2018
DOI: 10.17269/s41997-018-0157-z
|View full text |Cite
|
Sign up to set email alerts
|

Duration and intensity of different types of physical activity among children aged 10–13 years

Abstract: Objectives To use a predominately objective measurement approach to assess and describe: (1) the amount of time that children aged 10-13 years spend participating in outdoor active play, active travel, curriculum-based physical activity at school, and organized sport; (2) the movement intensity composition of these four types of physical activity (i.e., % of time spent at a sedentary, light, or moderate-tovigorous intensity); and (3) the proportion of each movement intensity obtained by participating in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
(31 reference statements)
0
12
0
1
Order By: Relevance
“…One of the most robust findings links time spent in outdoor play to physical activity, indicating that children playing outside are more physically active and less sedentary than when indoors [5,6]. A study of 10–13-year-old children and adolescents found that outdoor play contributed 36 min/day to physical activity, versus 40 min/day for organized sports, 17 min/day for active travel and 26 min/day for curriculum based physical activity [7]. Outdoor play has further been associated with motor, visual, and cognitive development, socio-emotional learning and mental health [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most robust findings links time spent in outdoor play to physical activity, indicating that children playing outside are more physically active and less sedentary than when indoors [5,6]. A study of 10–13-year-old children and adolescents found that outdoor play contributed 36 min/day to physical activity, versus 40 min/day for organized sports, 17 min/day for active travel and 26 min/day for curriculum based physical activity [7]. Outdoor play has further been associated with motor, visual, and cognitive development, socio-emotional learning and mental health [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…On study days during recess (i.e., 30-minute period of unstructured play under teacher supervision), the cohort sample wore elastic belts around their waist equipped with a Qstarz BT-Q1000XT Global Positioning System (GPS) device (Qstarz Intl Co., Taipei, Taiwan) and an Actigraph wGT3X-BT accelerometer (ActiGraph LLC, FL) to measure geographic location and physical activity levels, over time (38,39). We set sampling rates of 15 seconds for GPS devices and accelerometers (40,41).…”
Section: Measurement Of Geographic Location and Physical Activitymentioning
confidence: 99%
“…The location of green features will be joined to the time-matched device data, within GIS. Although previous studies have matched children's geographic location and physical activity levels over time (38)(39)(40)(41), this study enables assessment of a child's experienced heat index and physical activity level at any particular location.…”
Section: Time-matching Of Geographic Location Physical Activity Andmentioning
confidence: 99%
“…On study days during recess (i.e., 30-minute period of unstructured play under teacher supervision), the cohort sample wore elastic belts around their waist equipped with a Qstarz BT-Q1000XT Global Positioning System (GPS) device (Qstarz Intl Co., Taipei, Taiwan) and an Actigraph wGT3X-BT accelerometer (ActiGraph LLC, FL) to measure geographic location and physical activity levels, over time (45,46). We set sampling rates of 15 seconds for GPS devices and accelerometers (47,48).…”
Section: Measurement Of Geographic Location and Physical Activitymentioning
confidence: 99%
“…The location of green features will be joined to the time-matched device data, within GIS. Although previous studies have matched children' s geographic location and physical activity levels over time (45)(46)(47)(48), this study enables assessment of a child' s experienced heat index and physical activity level at any particular location.…”
Section: Time-matching Of Geographic Location Physical Activity Andmentioning
confidence: 99%